Irreversible laryngeal palsy: An induced complication of carboplatin 450mg/m2 and paclitaxel 250mg/m2 - Case report - Rawish Kumar; Sanjay K. Munjal; Naresh K. Panda (Otolaryngology Case Reports, 2018)
Introduction: Unilateral vocal cord paralysis is common than bilateral palsy and is mostly idiopathic in origin. Other causes may include malignancy, secondary to neck or recurrent laryngeal nerve trauma, intubation or secondary to surgery however, taxanes induces paresis which can lead to paralysis following paresis of larynx. Case summary: A female patient presented with cancer of cervix (Endometrium) and developed vocal cord paralysis after completion of five cycles of treatment with injections paclitaxel 250mg/m2 and carboplatin 450mg/m2. Patient's stroboscopic examination, electromyography (EMG) confined that one vocal cord lateralized in paramedian position. Voice analysis revealed low pitch and loudness and with breathy quality. Discussion: The vocal cord paralysis was believed to have occurred due to neurotoxic effect of carboplatin and paclitaxel, as an added complication of these drugs. Carboplatin and paclitaxel above than cumulative dose can induce bilateral or unilateral vocal cord paresis or sometimes paralysis also. The concurrent amount of dose used of carboplatin and paclitaxel might have contributed to this illness in patient.